Decisões estratégicas e performance exportadora: estudo na indústria gaúcha - Crespam, Cristina Ceribola (2010)
This study aims to verify the relation between strategic decisions and performance of exporting companies from Rio Grande do Sul state, Brazil. In addition, it is described the profile and the international performance characteristics. Besides, it is measured the performance of exporting companies in study. In order to reach the results, it were reviewed issues related to internationalization of business, entry modes, export performance, export marketing strategy and strategic types in order to guide the empirical research. A descriptive research was conducted with application of survey as a procedure for collecting data, which were analyzed by three techniques: a) descriptive statistics, b) analysis of variance, and c) Pearson correlation. The results showed that the surveyed companies are mostly small and medium businesses. The strategy that they most identified was the prospector, followed by the analyst. The most part of the surveyed companies positioned themselves as having from medium to substantial experience in international market. Considering aspects of international operations, the main entry mode used by companies was exportation, in addition, more than half the respondents negotiate with up to 10 countries and pointed out the intention to internationalize from beginning of its operations and the existence of request coming from client abroad as main reasons for internationalization. The obtained data also revealed that the clarity of the specification to the destination market, the high adaptation of the pack and the language of the product label to destination country and that over half of the products were consumer products with established position in the company. The surveyed companies marketed mainly with competitive or highly competitive countries, which showed medium cultural similarity and large potential demand. Considering the export performance, it is verified that the surveyed companies placed themselves at the extremes in terms of export intensity, performed predominantly around the mean response considering the economic, strategic and satisfaction of the export venture and were classified mostly as low performance. The results showed the existence of a relation between strategic decisions and export performance. Considering export performance, in strategic terms, it was noticed a difference in behavior between companies that have adopted different strategic types, and is evidenced a correlation between the variables of the marketing strategy of export and the dimensions of export performance.